What is the effectiveness and safety of serial intraarticular steroid injections of the knee?. Issue 10 (October 2017) - Montgomery, Stefan; Godenick, Mark; Hoover, Becky; Gainey, James Spencer; Klosterman, Scott
Abstract : EVIDENCE‐BASED ANSWER : In patients with osteoarthritis of the knee, serial intraarticular (IA) corticosteroid injections given every 3 months do not cause radiographic joint space narrowing at 2 years (SOR: B, single RCT). When single and serial injections are pooled, pain and function is improved in the short term (up to 6 weeks) but not the long term (after 13 weeks) (SOR: A, meta‐analysis of RCTs). Single injections maintain symptom improvement up to 24 weeks (SOR: A, meta‐analysis of RCTs).